226k views
2 votes
Solve 4(6-3) = 6 Put the steps in order to solve the equation from first to last.b= 4.5Distribute 4 to everything in parenthesis.Add 12 to both sides.Divide both sides by 4.

User NickGPS
by
4.7k points

1 Answer

3 votes

Given equation is:


4(b-3)=6

So from given steps follow:

1) put b=4.5

2) then distribute 4 to everything in parentheses.

3). add 12 to both sides.

4). divide both sides by 4.

Now the right hand side and left hand side become equal.

User HasaniH
by
4.4k points